Impacts of cage aquaculture on the farm dam ecosystem and its use as a multipurpose resource : implications for irrigation - Du Plessis, D. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScAgric (Conservation Ecology and Entomology)--University of Stellenbosch, 2007.